ANALISIS RETURN ON INVESTMENT PROYEK PEMBANGUNAN GOR KEROBOKAN TERHADAP PENGGUNAAN MODAL KERJA KONTRAKTOR - Wiranata, A.A. (Jurnal Ilmiah Teknik Sipil, 2012)
Evaluation on Cash Flow Project shows that cash inflows experiencing delays during June, July, August and November 2008. This however, is overcome by the use of working capital. It indicates that such project is sufficiently liquid. Project profitability of GOR Kerobokan in Badung regency reached Operating / Profit Margin of 15.1% indicating the company’s ability to generate operating profit in one period of the project amounted to 15.1%. The analysis shows that ROI = 16,827%, ROIbefore tax = 28.573% and ROIafter tax = 20.001%. These ROIs are greater than the profit margins that amounted to 15.1% and the effective rate of 15% per years. The investment analysis shows that NPV = IDR 77,672,800.77 using the discount rate (i) of 3%. The NPV is positive (+), the IRR = 3.196% per month and BCR = 1.0095. The IRR is larger than bank (BPD Bali) interest rate of 1.25% per month (IRR > i). BCR is greater than 1 indicating that GOR Kerobokan Development Project is financially feasible.
Keywords: Return On Investment, Projects Working Capital